2015
DOI: 10.1016/s2095-3119(15)61101-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dietary xylo-oligosaccharides for broilers fed a conventional corn-soybean meal diet

Abstract: An experiment was conducted to investigate the effect of dietary supplementation of xylo-oligosaccharides (XOS) on growth performance, meat quality, immune functions, duodenal morphology and intestinal microbial populations of broilers fed a conventional corn-soybean meal basal diet. A total of 450 1-d-old commercial Arbor Acres male broiler chicks were randomly allocated by bodyweight to 1 of 5 treatments with 6 replicate cages (15 broilers per cage) for each of 5 treatments in a completely randomized design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 26 publications
6
21
0
Order By: Relevance
“…Shi et al (2010) reported that the addition of xylo-oligosaccharides (XOS) decreased drip loss in the breast and thigh muscle of broilers. Similar results were also found in a study by Suo et al (2015), who suggested that such improvement could be attributed to an increased antioxidant capacity induced by XOS. Lee et al (2012) reported that the phenolic compounds in PESR exert potentially antioxidant properties that slow lipid peroxidation and improve meat quality in broilers.…”
Section: Improving Nutrition Utilization and Meat Quality Of Broiler supporting
confidence: 89%
See 1 more Smart Citation
“…Shi et al (2010) reported that the addition of xylo-oligosaccharides (XOS) decreased drip loss in the breast and thigh muscle of broilers. Similar results were also found in a study by Suo et al (2015), who suggested that such improvement could be attributed to an increased antioxidant capacity induced by XOS. Lee et al (2012) reported that the phenolic compounds in PESR exert potentially antioxidant properties that slow lipid peroxidation and improve meat quality in broilers.…”
Section: Improving Nutrition Utilization and Meat Quality Of Broiler supporting
confidence: 89%
“…The ability of fresh meat to retain moisture is one of the most important quality characteristics in raw products, both from the consumer and processor's point of view (Bowker & Zhuang, 2013). Loss in water-holding capacity (WHC) may cause liquid outflow that introduces loss of soluble nutrients and flavor (Lee et al, 2012;Bowker & Zhuang, 2013;Suo et al, 2015), but also causes unappealing moisture accumulation in packaging, a less tender cooked product as well as reduced functionality in the manufacturing of further processed poultry products (Bowker & Zhuang, 2013). As our results show, the higher protein percentage in both the breast meat of chickens fed 0.5% FSBH and the leg meat of all three treatment groups is accompanied by a higher WHC.…”
Section: Improving Nutrition Utilization and Meat Quality Of Broiler mentioning
confidence: 99%
“…This increase in the absorption surface area contributed to the absorption of minerals in the intestine. Similar to our results, some reports indicated that the duodenal villus height and crypt depth are also affected by XOS supplementation in chickens [ 13 , 35 ]. Because of the scarcity of available reports on the effects of XOS on villus height and crypt depth in rodent models, a comparison was made with other studies that used similar functional oligosaccharides.…”
Section: Discussionsupporting
confidence: 92%
“…A vitro study also indicated that XOS can stimulate greater bifidobacteria levels compared with other oligosaccharides [ 36 ]. Recently, research has shown that XOS (100 mg/kg or 75 mg/kg) can improve growth performance and strengthen humoral immunity in broilers [ 37 , 38 ]. However, a scarcity of reports exists on the use of XOS in weanling pigs’ diets.…”
Section: Discussionmentioning
confidence: 99%